Perceived Level of Skills Possessed by Technical College Students for Self-Employment in Winding of Electrical Machines Operations in Rivers State - Agwi, Vincent I. A.; Agbo, Nnaemeka Martin; Igbudu, Chimemezuo Felix (Journal of Research in Industrial Technology and Educational Studies, 2025)
The study assessed level of skills possessed in winding of electrical machines operation for self-employment among students in Technical Colleges in Rivers State. Three research questions and three hypotheses guided the study. The study adopted descriptive survey research design. The population of the study comprised 38 electrical installation and maintenance work trade teachers’ and 22 workshop instructors in the four government technical colleges owned by Rivers State government. The study adopted a census sampling technique because the population is of manageable size. The instrument used for data collection was a 23 items questionnaire structured in a-4 points rating scale. The instrument for the study was face and content validated by three experts in the Department of Technical Education, Ignatius Ajuru, University of Education, Rumuolumini, Port Harcourt. The reliability of the instrument was determined through Cronbach alpha reliability coefficient method. A total of 20 respondents who were not part of the population of the study were used in testing the reliability of the instrument, the reliability co-efficient of 0.75 was obtained. Mean and standard deviation were used to answer the research questions while t-test was used to test the hypotheses at 0.05 level of significance. The study found that students’ ability in dismantling of electrical machines will be an added advantage for employment or self- employment, students’ ability to remove and replace worn-out brushes accurately will be an added advantage for employment or self-employment upon graduation. Based on these finding, the study recommended among others that technical college students in Rivers State should be given the opportunity of real-life experience through exposure in industries/establishments as to enable them handle winding of electrical machines operation for self-employment upon their graduation.
Keywords: Skill; Winding; Electrical machine; operation; self-employment